2023
DOI: 10.1039/d3ma00324h
|View full text |Cite
|
Sign up to set email alerts
|

Pore size and electronic tuning in cerium-doped CoFe-LDH for the oxygen evolution reaction

Abstract: A series of cerium-doped CoFe-layered double hydroxides (LDH) materials were synthesized using a co-precipitation method, and they were utilized for oxygen evolution reaction. Among all the materials, CoFeCe2 having the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 102 publications
(160 reference statements)
1
10
0
Order By: Relevance
“…1–3 Limitless efforts to solve these issues lie in developing green energy technologies ( i.e. , fuel cells, 4 batteries, 5 and water splitting 6,7 ) and gas conversion reactions. 8–10 CO Oxid is formed during heterogeneous catalysis electrochemically, 11,12 or thermally, 13–16 but the latter is feasible for large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…1–3 Limitless efforts to solve these issues lie in developing green energy technologies ( i.e. , fuel cells, 4 batteries, 5 and water splitting 6,7 ) and gas conversion reactions. 8–10 CO Oxid is formed during heterogeneous catalysis electrochemically, 11,12 or thermally, 13–16 but the latter is feasible for large-scale applications.…”
Section: Introductionmentioning
confidence: 99%
“…In general, electrocatalysts with high electrical conductivity, large surface area, and high pore volume with optimized pore width can provide superior electrochemical performance for OER. 9 An electrocatalyst comprising these properties can provide plenty of active sites with enhanced charge-transfer properties. 10 In this regard, non-noble metalbased electrocatalysts (Co, Ni, Fe, etc.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The unsymmetrical electron occupancy in the t 2g orbitals of Co 2+ leads to a dynamic Jahn−Teller distortion, which results in the lengthening of the Co−O bonds and further facilitates the formation of O−O bonds during the OER process. 9 ZIF-67, a cobalt-based zeolitic imidazolate framework (ZIF), in which Co 2+ ions are linked with 2-methyl imidazole, is one such candidate for this purpose. 20 It has a very high surface area and uniform pore size distribution, having a pore width of ∼1.01 nm, making it a good candidate for catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,13 For practical applications of nanomaterials in catalysis or charge storage, pore size is an important parameter since narrow pore size can greatly enhance the number of active sites. 5,14 For instance, Gogotsi and co-workers reported that the presence of ultramicropores (<1 nm) in nanomaterials results in a massive increase in the charge storage capacity for supercapacitor application. 15,16 However, for electrocatalysis, it can be envisioned that a somewhat wider pore size will be ideal to avoid pore bursting due to product accumulation inside micropores.…”
Section: ■ Introductionmentioning
confidence: 99%